Issues Confronting the Stock Markets in a Period of Rising Institutionalization - Freund, William C. (Journal of Financial and Quantitative Analysis, 1972)
The facts of increased institutional trading on the nation's securities markets are by now well known. On the New York Stock Exchange (NYSE), the six major institutional groups—insurance companies, investment companies, noninsured pension funds, nonprofit institutions, common trusts, and mutual savings banks, now own more than one-fourth of the market value of listed shares compared with less than 16 percent at the end of 1956. But, ownership is merely the tip of the perennial iceberg, since institutional trading of stock has become much more significant than institutional ownership. This fact is pointed up in the recent SEC Study of Institutional Investors. It shows that there has been a relatively slow increase in the share of outstanding stock owned by institutions in all markets, but the institutional share of trading has mushroomed.